Endoscopic diverticulotomy for Killian-Jamieson diverticulum: mid-term outcome and description of an ultra-short tunnel technique - Modayil, Rani J.; Zhang, Xiaocen; Ali, Mohammad; Das, Kanak; Gurram, Krishna; Stavropoulos, Stavros N. (Endoscopy International Open, 2022)
Background and study aims Killian-Jamieson Diverticulum (KJD) is a rarer and more recently described upper pharyngeal diverticulum than Zenker’s diverticulum (ZD). KJD is more difficult to manage than ZD because it tends to extend lower into the upper mediastinum and the diverticulum neck is in close proximity to the recurrent laryngeal nerve. There is limited literature on KJD management and transcervical surgical diverticulectomy is the mainstay of therapy. Patients and methods Here we describe two methods of endoscopic diverticulotomy to treat KJD – direct and tunneling diverticulotomy (with hypopharyngeal tunnel or ultra-short tunnel – the latter being our preferred technique). Results This was a retrospective study including 13 consecutive patients between March 2015 and April 2018. Three patients received direct and 10 received tunneling diverticulotomy (7 with the hypopharyngeal tunnel and 3 with the ultra-short tunnel). All procedures were completed in 16 to 52 minutes. There was no incidence of bleeding, mediastinitis, or sign of recurrent laryngeal nerve injury. At follow up of 9 to 79 months (median 33), the clinical success rate was 92 % (12/13); 11 patients had complete symptom resolution (post-operative symptom score = 0) and one patient had near-complete symptom resolution (occasional residual dysphagia). One patient receiving direct myotomy had limited symptom relief (frequent residual dysphagia and occasional residual regurgitation), possibly related to incomplete myotomy. Conclusions Endoscopic tunneling diverticulotomy is a feasible, safe, and effective method to treat KJD.